1985
DOI: 10.1071/ea9850440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of fungicides for control of stem rust of wheat

Abstract: The potential commercial use of fungicides for control of stem rust (Puccinia graminis) of wheat was assessed in field experiments at two sites. Foliar sprays containing either triadimefon or propiconazole were the most effective in reducing disease severity. Chlorothalonil was effective only when applied at an early stage of disease development and where stem rust was not severe in control plots. Dichlone, fenarimol, nuarimol and 2-(thiocyanomethylthio) benzothiazole did not significantly reduce stem rust sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…When long duration of control was required, a single fungicide application at disease onset was equally effective as that applied after a 3-week delay, but was inferior to application at both times. Mayfield (1985) identified the triazole fungicides propiconazole and triadimefon as being moderately effective in control of stem rust of wheat but found that the resultant increases in grain yield and quality were barely sufficient to justify the cost of treatment at that time. In the current study, Folicur (tebuconazole) provided more consistent results in terms of disease control and yield increase than Triad (triadimefon) or Impact (flutriafol).…”
Section: Discussionmentioning
confidence: 97%
“…When long duration of control was required, a single fungicide application at disease onset was equally effective as that applied after a 3-week delay, but was inferior to application at both times. Mayfield (1985) identified the triazole fungicides propiconazole and triadimefon as being moderately effective in control of stem rust of wheat but found that the resultant increases in grain yield and quality were barely sufficient to justify the cost of treatment at that time. In the current study, Folicur (tebuconazole) provided more consistent results in terms of disease control and yield increase than Triad (triadimefon) or Impact (flutriafol).…”
Section: Discussionmentioning
confidence: 97%
“…This is a particularly valuable finding in light of the recently reported exploration of monosubstituted 1,2‐ethanedithiols (similar to 9i ) as zinc‐binding groups on natural product largazole analogs for the development of histone deacetylase inhibitors . S–H insertion product 9j clearly belongs to the 2‐alkylthiobenzothiazole scaffold widespread in the bioactive compound domain . We also attempted to involve diazo lactam 7a in the reaction with thiobenzoic acid but no corresponding product was observed.…”
Section: Resultsmentioning
confidence: 87%
“…This stimulatory effect of fungicide treatments on growth may result in significant yield increases even in the absence of the disease (Wegulo et al, 1998). Fungicide treatments, if applied under high and moderate disease pressure at critical growth stages may reduce large yield losses by suppressing or eliminating stem rust pathogen (Mayfield, 1985). However, greater rust control and greater yield increases may have been possible using higher rates and more applications of fungicides as well as spraying at an earlier stage of the rust epidemic.…”
Section: Discussionmentioning
confidence: 97%
“…Dill-Mackey et al (2000) induced severe stem rust epidemics in barley and wheat and observed yield losses of 50 to 58%. Mayfield (1985) found a clear relationship between grain yield and disease severity by demonstrating that prevention of a 1% increase in rust severity saved a 2% loss in grain yield. Different fungicides vary in their efficacy to control stem rust.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation